Management of Concomitant Intrusion and Complicated Crown-Root Fracture Injury of Maxillary Central Incisors in a Child - Tariq Abu Haimed; Samah S. Abdeltawab; Rayyan A. Kayal; Mona H. Almotairi; Khalid H. Zawawi (Hindawi Limited, 2023)
Dental intrusions are a severe type of injury because they impact the neurovascular supply of the tooth as well as the supporting tissues which predispose the tooth to necrosis and root resorption. Management of these injuries requires repositioning of the teeth under close monitoring to avoid complications. The management becomes more comprehensive when an intrusion is combined with other injuries, such as a crown-root fracture. This case report represents a 4-year follow-up of a child who suffered from a concomitant injury of intrusion and complicated crown-root fracture to the maxillary immature permanent central incisors. The management involved a multidisciplinary approach including endodontics, pedodontics, orthodontics, periodontics, and prosthodontics. Given the guidelines of dental trauma and the circumstances of the case, the fractured teeth were root canal treated, filled with a bioceramic plug and gutta-percha, and then restored with posts/cores and temporary crowns. The intrusion was managed initially by passive eruption followed by an active orthodontic eruption, after which the teeth were restored with permanent ceramic crowns. Throughout the course of treatment, the teeth showed no complications of root resorption or ankylosis, although one tooth developed a periapical infection which was managed by apical surgery. At the 4-year follow-up, the teeth revealed healthy periodontium and good esthetics.